1990
DOI: 10.1080/01688639008400991
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and nonverbal communication of events in learning-disability subtypes

Abstract: This study compared a group of nondisabled children (ND) with groups of learning-disabled children who were primarily impaired in reading and arithmetic skills (Reading-Arithmetic Disabled; RAD) and arithmetic but not reading (Arithmetic Disabled; AD) on a set of tasks involving comprehension and production of verbally and nonverbally presented events. Children viewed videotaped scenarios presented in verbal (narrative) and nonverbal (puppet actors) formats and were asked to describe or enact with puppets the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 22 publications
3
20
0
1
Order By: Relevance
“…One hypothesis is that children with learning disabilities, and particularly children with nonverbal learning disabilities, have difficulty processing social cues. The results of two studies that included subtyping methodology (Loveland et al, 1990;Ozols & Rourke, 1985) suggest that there is an interaction between learning disability subtype and perception of social cues. This interaction appears to be complex and deserves further study using subtyping measures that have demonstrated reliability in previous studies.…”
Section: Such Studies Include Investigations By Wiener Et Al (1990)mentioning
confidence: 95%
See 3 more Smart Citations
“…One hypothesis is that children with learning disabilities, and particularly children with nonverbal learning disabilities, have difficulty processing social cues. The results of two studies that included subtyping methodology (Loveland et al, 1990;Ozols & Rourke, 1985) suggest that there is an interaction between learning disability subtype and perception of social cues. This interaction appears to be complex and deserves further study using subtyping measures that have demonstrated reliability in previous studies.…”
Section: Such Studies Include Investigations By Wiener Et Al (1990)mentioning
confidence: 95%
“…To validly address this question, investigators would have to group participants with learning disabilities by subtype before assessing their abilities to interpret social cues. Two studies were found that included such methodology: one by Ozols and Rourke (1985), and one by Loveland, Fletcher, and Bailey (1990). Ozols and Rourke (1985) reported that on measures of social perception involving verbal labeling and explanations, clinic-identified children with language disabilities were more impaired than both nondisabled children and children with other types of learning disabilities.…”
Section: Such Studies Include Investigations By Wiener Et Al (1990)mentioning
confidence: 96%
See 2 more Smart Citations
“…Applying this approach, a number of subtypes of LD based on patterns of academic and neuropsychological assets and de®cits were generated. Their reliability and validity have been the subject of considerable scienti®c scrutiny in a number of laboratories (Loveland, Fletcher, & Bailey, 1990;Share, Mof®tt, & Silva, 1988;Silver, Pennett, Black, Fair, & Balise, 1999;White, Mof®tt, & Silva, 1992). (See Greenham [1999], Little [1993], Rourke & Fuerst [1992], and Rourke [2000] for reviews of this and related work.…”
mentioning
confidence: 99%